2000
DOI: 10.1094/cchem.2000.77.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Dough Microextensibility Method Using a 2‐g Mixograph and a Texture Analyzer

Abstract: Cereal Chem. 77(1):39-43Development of a small-scale method to measure dough extensibility, using a 2-g mixograph and the TA.XT2 texture analyzer (TA) equipped with Kieffer rig, suitable for early-generation wheat quality screening is presented. Three hook speeds 3.3, 7.0, and 10.0 mm/sec were tested on the TA. Only at the lower hook speed of 3.3 mm/sec were wheats, varying in quality, clearly differentiated. The ability to differentiate between wheats using the TA was compared with the Brabender Extensigraph.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 7 publications
0
34
0
Order By: Relevance
“…Area under the force vs. distance curve (mm 2 ) (Dobraszczyk & Salmanowicz, 2008). It was reported that the parameters obtained by using the Kieffer extensibility rig were significantly correlated with the Extensograph parameters especially those related to the strength of dough (Suchy et al, 2000;Grausgruber et al, 2002;Mann et al, 2005;Ktenioudaki et al, 2011). The reason why the extensibility parameters were not exhibit such a high correlation as strength parameters was explained by the differences in the sample size and strain rate between the two methods (Ktenioudaki et al, 2011).…”
Section: Fig 7 Kieffer Force-distance Curvementioning
confidence: 99%
“…Area under the force vs. distance curve (mm 2 ) (Dobraszczyk & Salmanowicz, 2008). It was reported that the parameters obtained by using the Kieffer extensibility rig were significantly correlated with the Extensograph parameters especially those related to the strength of dough (Suchy et al, 2000;Grausgruber et al, 2002;Mann et al, 2005;Ktenioudaki et al, 2011). The reason why the extensibility parameters were not exhibit such a high correlation as strength parameters was explained by the differences in the sample size and strain rate between the two methods (Ktenioudaki et al, 2011).…”
Section: Fig 7 Kieffer Force-distance Curvementioning
confidence: 99%
“…• C and 85% relative humidity (RH), according to Suchy et al 23 After resting, four dough strips from each replicate dough were tested for their extensibility properties on a texture analyzer (TA-HD, Texture Technologies Corp., Scarsdale, NY, USA) equipped with a Stable Micro Systems/Kieffer dough and gluten extensibility rig. This was used with a hook extension speed of 3.3 mm s −1 and a trigger force of 1 g, using a 50 kg load cell.…”
Section: Measurements Of the Textural Properties Of Doughmentioning
confidence: 99%
“…The farinograph test (AACC method 54-41) 35 measured water absorption (FAB), dough development time (DDT), dough stability (STA) and mixing tolerance index (MTI). The dough microextension test 36 was performed using a TA.XT2 texture analyser (Texture Technologies Corp, Scarsdale, NY, USA/Stable Microsystems, Godalming, UK). Dough samples were mixed in the 2 g mixograph with a 2% salt solution at FAB plus 5% additional water 36 to determine MDT.…”
Section: Technological Testsmentioning
confidence: 99%